The association between research design and the perceived treatment effectiveness: a cross-sectional study - Bralić, Nensi; Buljan, Ivan (Frontiers in Medicine, 2023)
Objective: To evaluate the impact of research design on the perceived medical treatment effectiveness among researchers, healthcare workers (HCW) and consumers in Croatia.Methods: A cross-sectional study was conducted from November 2021 to February 2022 using an online survey. The participants were researchers, healthcare workers and consumers from Croatia. The survey had six scenarios about the same medical treatment presented within different study designs and in random order. Participants were asked to assess on a scale from 1-10 if the descriptions presented a sufficient level of evidence to conclude that the treatment was effective.Results: For researchers (n=97), as the number of participants and degree of variable control in the study design increased, the perceived level of sufficient evidence also increased significantly. Among consumers (n=286) and HCWs (n=201), no significant differences in scores were observed between the cross-sectional study, cohort study, RCT, and systematic review.Conclusions: There is a need to implement educational courses on basic research methodology in lower levels of education and as part of Continuing Medical Education for all stakeholders in the healthcare system.Trial registration: This study has been registered on the Open Science Framework prior to study commencement (https://osf.io/t7xmf).